Peningkatan Keaktifan dan Hasil Belajar IPS Menggunakan Aplikasi Google Form di Kelas 1G Madrasah Muallimin Muhammadiyah Yogyakarta - Mutakin, Mohamad Deden (Jurnal Kiprah, 2022)
In online learning there are obstacles to student activity in collecting assignments so that it affects learning outcomes. The use of google forms is considered to be able to increase student activity and learning outcomes. The purpose of this study was to determine the increase in the collection of active assignments using google form in class 1 G Multilingual Tsanawiyah in social studies learning at Madrasah Mu'allimin Muhammadiyah Yogyakarta. This research is classroom action research using Kemmis and McTaggart models. The research instrument used was an observation sheet on the activity of collecting student assignments and CBT questions that had been set on the google form. The data analysis used is quantitative data analysis which is described descriptively. The results showed that the google form application was able to increase the achievement of increasing active task collection and student learning outcomes.